Optimal Design of Vehicle Structure Based on Computer-Aided Technology - Guang Bai (Journal of Electrical and Computer Engineering)
In order to improve the optimization design effect of modern automobile vehicle structure, this paper combines computer-aided technology to carry out vehicle structure optimization design, introduces the material description of the collision process, expounds the boundary conditions in the collision process, and introduces the theory of explicit integration algorithm. In the simulation process, it is necessary to deal with time step control, contact algorithm, hourglass control, etc., and analyze the optimization method of automobile collision, which is divided into experimental design and optimization method. In addition, the experimental design mainly introduces the orthogonal experimental design, which is applied to the lightweight design of automobile structures. The research verifies that computer-aided technology can play an important role in vehicle structure optimization and effectively improve the scientificity of vehicle structure design.